LANDASAN HUKUM DAN PRINSIP-PRINSIP ASURANSI SYARIAH DI INDONESIA - Dara Nabila; Zainarti Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Sharia insurance is a type of financial institution that functions in accordance with Islamic sharia, which upholds the concept of mutual protection (takaful) and mutual assistance (ta'awun). This thinking is regulated in Indonesian laws and regulations, including DSN-MUI Fatwa No. 21/DSN-MUI/X/2001, and is based on the teachings of the Koran, hadith, ijma, and ulama fatwas. Its guiding principles include mutual protection, cooperation in virtue, and avoiding aspects of riba, gharar (uncertainty), maisir (gambling), and activities that violate sharia. Islamic insurance offers Muslims a way to fulfill their risk protection requirements in line with Islamic principles, according to this research, which combines descriptive techniques with literature review methods. Sharia insurance builds a transparent and socially responsible financial system through the application of fair principles and a strong legal basis.